Editorial. Issue 12 (December 2019) - Mansfield-Devine, Steve
Abstract : If you ever need an example of how cyber security technology is a two-edged sword, you need look no further than Israeli security company NSO Group. Depending on what you choose to believe, it is either enabling repressive regimes to subjugate their citizens or is empowering law enforcement to combat terrorists, paedophiles and other existential threats to society. Maybe both.